PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING DENGAN APLIKASI ZOOM DALAM MENINGKATKAN HASIL BELAJAR MATA KULIAH PENGANTAR DASAR MATEMATIKA - I Komang Sukendra (Widyadari : Jurnal Pendidikan, 2021)
The purpose of this study was to determine whether there was a student response or to improve the student's ability to answer mathematics induction questions in the Basic Mathematics Introduction course by applying the problem solving learning model through the Zoom application. This type of research is classroom action research. This research was conducted in the Mathematics Education Study Program of the PGRI Mahadewa University of Indonesia. The subjects of action research were students in semester 1 of Mathematics Education at PGRI Mahadewa University in Indonesia for the academic year 2020/2021, and the object of this research was the study of understanding mathematics induction material in basic introductory mathematics courses and student responses to problem solving learning models. In this study, two cycles were used and each cycle went through four stages of the activity process which included (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. Data collection techniques in this study are using test and observation methods. Retrieval of data using observation techniques for qualitative data. The results of the action research are (1) There is a student response in the ability to answer math induction questions, (2) the application of problem solving learning models with the zoom application can improve the ability to answer math induction questions in the basic introductory mathematics course.